Non-equilibrium joule heat preparation of two-dimensional nitrogen-doped carbon-coated SiO x Method for c-negative electrode and use
Patent Information
- Application Number
- CN202610910030.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]有鉴于此,本发明提供了一种非平衡焦耳热制备二维氮掺杂碳包覆SiOx@C负极的方法及应用,采用限域插层与非平衡焦耳热转化的协同改性策略,在硅氧烯片层的层间间隙及表面原位构筑均匀连续的氮掺杂碳导电网络,有效解决了现有硅氧烯基负极材料本征导电性差、脱嵌锂过程体积膨胀严重及界面稳定性不足的固有缺陷
[0009]上述技术方案的有益效果是:冰浴条件下的盐酸刻蚀可以选择性脱除CaSi2层间的Ca2+,温和的反应条件可以避免刻蚀过程破坏硅氧烯的二维层状结构,超声剥离可以进一步打开堆叠的片层,冷冻干燥可以有效防止硅氧烯纳米片在干燥过程中发生不可逆团聚,保证二维片层的完整结构。
Smart Images

Figure CN122991968A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy storage materials technology, specifically relating to nitrogen-doped carbon-coated SiO2 prepared based on two-dimensional layered siloxanes and combined with a non-equilibrium flash Joule heating process. x @C composite materials, their preparation methods, and applications. Background Technology
[0002] Lithium-ion batteries possess outstanding advantages such as high energy density, long cycle life, and environmental friendliness, and are widely used in consumer electronics, new energy vehicles, and large-scale energy storage. The anode material is a key factor determining the energy density of lithium-ion batteries; currently, the theoretical specific capacity of commercially available graphite-based anodes is only 372 mAh g⁻¹. -1 This is no longer sufficient to meet the development needs of high-energy-density lithium-ion batteries.
[0003] Among non-carbon anode materials, silicon-based materials have a capacity of 4200 mAh g. -1 Silicon, with its ultra-high theoretical specific capacity, suitable lithium insertion / extraction potential, and abundant reserves, is widely recognized as the preferred anode material for next-generation high-energy-density lithium-ion batteries. However, the volume expansion of silicon-based materials during lithium insertion / extraction can reach 300%–400%, easily leading to active particle pulverization, repeated SEI film rupture and failure, and electrode structure collapse, resulting in rapid capacity decay and severely restricting its industrial application. Existing research shows that two-dimensional layered siloxenes naturally possess a layered stacked structure and nanoscale interlayer voids, which can pre-reserve space for lithium insertion volume expansion. Compared with traditional bulk silicon and ordinary nano-silicon, it can significantly alleviate volume deformation and exhibit superior cycle stability. However, two-dimensional siloxenes still have inherent defects such as poor intrinsic conductivity and low initial coulombic efficiency, which can lead to poor rate performance and initial capacity loss in full cells. How to effectively modify and optimize them to improve electrochemical performance is a problem that urgently needs to be solved by those skilled in the art.
[0004] To address the aforementioned shortcomings, carbon coating is currently the most industrially promising modification method, capable of simultaneously improving conductivity and buffering volume expansion. The industry commonly employs traditional tube furnace isothermal annealing for extended periods to carbonize the carbon source. However, this traditional process has significant technical limitations: due to the poor thermal stability of two-dimensional siloxanes, prolonged high temperatures can easily lead to irreversible collapse of the layered structure and closure of internal pores, causing them to lose their volume expansion buffering space; furthermore, the heating rate of traditional tube furnaces is relatively low, and the carbon source is prone to agglomeration and uneven graphitization under slow heating equilibrium, resulting in limited improvement in material conductivity.
[0005] Therefore, how to fully retain and leverage the unique advantages of the lithium intercalation volume expansion buffer structure of two-dimensional layered siloxanes, while effectively overcoming the technical limitations of traditional tube furnace long-term isothermal annealing carbonization processes, and developing an efficient carbonization modification technology adapted to the intrinsic structural characteristics of two-dimensional layered silicon-based materials, is a core technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] In view of this, the present invention provides a method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating. x The method and application of the @C anode employ a synergistic modification strategy of confined intercalation and non-equilibrium Joule thermal conversion to construct a uniform and continuous nitrogen-doped carbon conductive network in situ within the interlayer gaps and surface of siloxane sheets. This effectively solves the inherent defects of existing siloxane-based anode materials, such as poor intrinsic conductivity, severe volume expansion during lithium insertion / extraction, and insufficient interface stability. To achieve the above objectives, the present invention adopts the following technical solution: A non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO x The @C anode material has an accordion-like layered structure, wherein the SiO x The C composite material has a layered structure in the vertical direction, and the SiO x The particle size of the @C composite material is 1 to 12 μm, and there are nanometer-wide slits between any adjacent layers, with the width of the slits being 10 to 120 nm.
[0007] The above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO x The method and application of @C negative electrode include the following steps: (1) Preparation of siloxane material: Prepare a hydrochloric acid solution with a concentration of 0.5-12 M. Under ice bath stirring, slowly add CaSi2 to the prepared hydrochloric acid solution. After the reaction is complete, wash the product with water until neutral, and then perform ultrasonic exfoliation treatment for 1 h. After filtration, freeze dry at -40 to -50 ℃ to obtain siloxane material. (2) Preparation of composite precursor (Siloxene@PPy) by in-situ polymerization: Add siloxene material to 50-100 mL of carbon source dispersion, sonicate at 200-500 W, add oxidant, and then stir at 0-10 ℃ ice bath for 5-12 h. After the polymerization reaction is completed, wash the product with water until neutral, dry and collect Siloxene@PPy; (3) Obtaining the target material by flash carbonization: The above-mentioned Siloxene@PPy is placed in a flash Joule heating device and subjected to instantaneous high-temperature carbonization under an inert atmosphere. After the treatment is completed, two-dimensional nitrogen-doped carbon-coated SiO2 can be obtained. x @C composite material.
[0008] Preferably, in the above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ x In the method of the @C negative electrode, the ratio of CaSi2 to hydrochloric acid solution in step (1) is 1 g: (20-50) mL; the ice bath reaction temperature is 0-10 ℃, and the reaction time is 20-30 h.
[0009] The beneficial effect of the above technical solution is that hydrochloric acid etching under ice bath conditions can selectively remove Ca from the CaSi2 layers. 2+ Mild reaction conditions can prevent the etching process from damaging the two-dimensional layered structure of siloxane, ultrasonic exfoliation can further open up the stacked sheets, and freeze drying can effectively prevent irreversible aggregation of siloxane nanosheets during the drying process, thus ensuring the integrity of the two-dimensional sheet structure.
[0010] Preferably, in the above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ x In the preparation method of the @C negative electrode, the concentration of the siloxane material in step (2) is 0.5–2 mg / mL. -1 The carbon source dispersion is a pyrrole aqueous solution, and the mass ratio of siloxane material to carbon source is 1:(0.4-2). The added oxidant is FeCl3, and the molar ratio of pyrrole monomer to FeCl3 is 1:(1.5-2.5).
[0011] The beneficial effects of the above technical solution are: the small size of the pyrrole monomer allows it to smoothly enter the interlayer gaps of the siloxene. During the in-situ polymerization process, a polypyrrole layer will grow uniformly in the interlayer and on the surface of the siloxene without destroying the intrinsic layered structure of the siloxene. At the same time, FeCl3, as an oxidant, can ensure that the polymerization reaction proceeds gently, avoid pyrrole agglomeration caused by excessive polymerization, and ensure the uniformity of Siloxene@PPy.
[0012] Preferably, in the above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ x In the method for the C negative electrode, the stirring speed of the water washing in step (2) is 300-800 r / min. -1 The washing temperature is 20–30 °C, the washing time is 2–6 h, and the washing continues until the pH of the filtrate is 6–7.
[0013] The beneficial effects of the above technical solution are: thorough water washing can remove the FeCl3 oxidant remaining from the polymerization reaction and unreacted small molecule impurities, avoiding the impact of impurity residues on subsequent carbonization treatment and the purity of the final material, and ensuring the cleanliness of the obtained Siloxene@PPy.
[0014] Preferably, in the above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ xIn the method of @C negative electrode, the drying method in step (2) is vacuum drying, the vacuum drying temperature is 60-80 ℃, and the drying time is 8-12h.
[0015] The beneficial effects of the above technical solution are: vacuum drying can complete the drying of Siloxene@PPy in a low-oxygen environment, preventing the oxidation of siloxene and polypyrrole during the drying process, and avoiding agglomeration during ordinary drying.
[0016] Preferably, in the above-mentioned preparation of two-dimensional layered nitrogen-doped carbon-coated SiO using non-equilibrium flash Joule heating... x In the @C negative electrode material method, step (3) refers to an atmosphere of N2, Ar or H2 / Ar mixture.
[0017] The beneficial effects of the above technical solution are: flash carbonization under an inert atmosphere can prevent the carbon layer and siloxane from oxidizing at high temperatures, ensure the high conductivity of the nitrogen-doped carbon layer, and avoid introducing impurities that affect the electrochemical performance of the material.
[0018] Preferably, in the above-mentioned non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ x In the method for the @C negative electrode, the specific operating parameters for the flash Joule heating in step (3) are as follows: the heating rate is 10 3 ~10 4 K s -1 The processing temperature is 500–900 ℃, and the processing time is 60–180 s.
[0019] The beneficial effects of the above technical solution are: the non-equilibrium ultrafast heating and rapid quenching process can ensure that polypyrrole is rapidly converted into a continuous nitrogen-doped carbon layer, and can also avoid the crystallization rearrangement of siloxane at high temperature, retain its amorphous mixed silicon oxide structure, which is conducive to achieving stable bonding at the interface.
[0020] This invention also discloses a method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating via the above method. x @C negative electrode material, the SiO x @C composite material is directly used as the negative electrode material for lithium-ion batteries; or the SiO2 composite material is used directly as the negative electrode material for lithium-ion batteries; x @C composite material is used as a negative electrode active material. It is mixed with conductive agents and binders to serve as a negative electrode material and is applied in high-energy-density lithium-ion batteries composed of negative electrode, positive electrode, separator and electrolyte.
[0021] As can be seen from the above technical solution, compared with the prior art, the present invention discloses a method for preparing two-dimensional layered nitrogen-doped carbon-coated SiO using non-equilibrium flash Joule heating. x@C anode materials and their applications have the following advantages and beneficial effects: The uniform and continuous carbon layer constructed in situ on the surface and between the layers of the composite material forms a conductive network, which significantly improves the overall electronic conduction rate of the material and fundamentally solves the inherent defect of poor intrinsic conductivity of siloxane. At the same time, the flexible carbon layer and the layered framework of siloxane form a synergistic buffer structure, which can further improve the negative impact of volume changes during the lithium insertion and extraction process of silicon-based materials, suppress the pulverization of active particles and the detachment of the conductive network, and greatly improve the structural stability and cycle life of the electrode.
[0022] By selecting pyrrole as the intrinsic carbon-nitrogen dual source, no additional nitrogen doping agent is required, simplifying the process. Uniform nitrogen doping into the carbon framework introduces numerous lattice defects and active sites, significantly enhancing the intrinsic electronic conductivity of carbon materials. Furthermore, it optimizes the SEI film, lowers the ion migration barrier, and improves charge-discharge kinetics. Compared to traditional pure carbon coating and exogenous nitrogen doping, this approach offers more uniform nitrogen doping, controllable carbon content, and higher electrochemical activity.
[0023] Abandoning the industry-standard long-duration isothermal tube furnace annealing, a non-equilibrium instantaneous high-temperature process is adopted, which eliminates prolonged high-temperature dwell time, fully preserving the two-dimensional lamellar morphology and pore structure, and maintaining the structural advantages of two-dimensional materials; the short-duration high temperature effectively suppresses the thermal volatilization of nitrogen, ensuring the stability and uniformity of nitrogen doping, avoiding the problems of nitrogen loss and uneven doping in traditional processes, and effectively alleviating carbon layer shedding during cycling. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0025] Figure 1 This is a SEM image of the layered silicate material from Example 1 of the present invention; Figure 2 The infrared spectrum of the layered silicate material in Example 1 of this invention is shown. Figure 3 Example 2 of the present invention: SiO x Test results of specific surface area and pore size distribution of @C composite material; Figure 4 Example 2 of the present invention: SiO x SEM image of the @C composite material; Figure 5 Example 2 of the present invention: SiO x@C composite material at 0.01–1.5 V, 0.2 A g -1 First charge-discharge curves at current density; Figure 6 Example 2 of the present invention: SiO x Rate performance curves of @C composite material at different current densities from 0.01 to 1.5 V; Figure 7 Example 2 of the present invention: SiO x @C composite materials at 0.01–1.5 V and 1 Ag -1 Cyclic performance curves at current density; Figure 8 Example 2 of the present invention: SiO x @C composite material at 0.01–1.5 V, 0.2 A g -1 Cyclic performance curves at current density; Figure 9 Example 3 of the present invention: SiO x SEM image of the @C composite material; Figure 10 Example 3 of the present invention: SiO x The first two charge-discharge curves of the @C composite material. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example
[0027] This embodiment describes a method for preparing a layered silicate material, with the following specific steps: Under ice bath stirring conditions, 2 g of CaSi2 powder was slowly added to 100 mL of a 5 mol / L solution. -1 The reaction was carried out in an HCl solution for 24 hours. The solution color changed from black to yellow-green. After the reaction was completed, the product was collected by filtration.
[0028] The product was thoroughly washed with deionized water and ethanol until the filtrate was neutral; then the product was dispersed in deionized water, sonicated at 300 W for 20 min, and finally freeze-dried at -50 ℃ for 12 h to obtain siloxane nanosheets.
[0029] The two-dimensional siloxane nanosheet material obtained in Example 1 of the present invention was tested as follows: The SEM image of the layered siloxane material prepared in Example 1 of this invention is shown below. Figure 1 As shown in the figure, this layered silicon material has a micron-scale size and a layered structure. The unique layered structure has multiple advantages: it is conducive to the uniform transfer of heat during the subsequent flash Joule heating process, it can provide sufficient channels for the rapid diffusion of lithium ions, and it can effectively buffer the volume changes of silicon-based materials during the charging and discharging process.
[0030] The infrared spectral characterization results of the layered two-dimensional siloxane material prepared in Example 1 of this invention are as follows: Figure 2 As shown, 3420cm -1 The broad absorption peak at 1078 cm⁻¹ corresponds to the stretching vibration of hydroxyl groups (-OH) on the material surface. -1 The strong characteristic peak at 802 cm⁻¹ is attributed to the asymmetric stretching vibration of the Si-O-Si bond. -1 With 960 cm -1 The absorption peaks at these locations correspond to the symmetric stretching vibration of the Si-O bond and the bending vibration of the Si-OH bond, respectively. These characteristic peaks are in perfect agreement with the intrinsic functional group structure of two-dimensional siloxanes. Example
[0031] To improve the conductivity and structural stability of the layered two-dimensional siloxane, the layered silicon material obtained in Example 1 was composited with polypyrrole. The specific steps are as follows: First, 150 mg of siloxane nanosheets were dispersed in 100 mL of deionized water and stirred under ice bath conditions to form a uniform suspension.
[0032] Subsequently, 75 μL of pyrrole monomer was slowly added under vigorous stirring. Then, after sonication at 300 W for 20 min, ferric chloride (FeCl3) solution was added dropwise as an oxidant, controlling the molar ratio of pyrrole to FeCl3 to be 1:2 to initiate polymerization. The polymerization reaction was carried out with continuous stirring at 0 °C for 8 h.
[0033] After completion, the product was thoroughly washed with deionized water until neutral and then vacuum dried at 80 °C for 12 h to obtain the Siloxene@PPy composite material.
[0034] The prepared Siloxene@PPy precursor was placed in a Joule heating apparatus and subjected to flash Joule heating (FJH) treatment with a burst of high current. The process achieved a heating temperature of approximately 700 °C, and the heat treatment was completed after 120 s.
[0035] A non-equilibrium reaction environment was established through ultrafast heating and rapid quenching, ultimately yielding the target product SiO. x @C.
[0036] The SiO prepared in Example 2 of this inventionx The specific surface area test results of the @C composite material are as follows: Figure 3 As shown, its specific surface area is 32 m². 2 g -1 The pore size distribution ranges from 2 to 30 nm, with an average pore diameter of approximately 5.7 nm.
[0037] The SiO prepared in Example 2 of this invention x SEM image of @C composite material as shown below Figure 4 As shown.
[0038] The SiO obtained in Example 2 of this invention x The electrochemical performance of the @C composite material was tested as follows: A negative electrode sheet is prepared by coating a slurry onto the surface of a copper foil. The slurry is composed of active material, Li-PAA and Super P conductive carbon black. All components are uniformly dispersed in deionized water by stirring for 12 h.
[0039] After processing, the copper foil coated with the slurry was cut into circular electrodes with a diameter of 14 mm and pressed under a certain pressure. It was then dried at 80 °C for 10 h. A lithium sheet was used as the counter electrode. The electrolyte was prepared by adding 1 mol / L of EC / DEC mixed solvent in a 1:1 volume ratio. -1 The LiPF6 is incorporated with 10% by volume of fluoroethylene carbonate.
[0040] Celgard 2500 membrane was selected as the battery separator, and CR2025 button cells were assembled in an argon-filled glove box.
[0041] The experimental battery was subjected to charge-discharge cycle testing using the Xinwei electrochemical test channel, with a charging cutoff voltage of 1.50V and a discharging cutoff voltage of 0.01V.
[0042] The test results are attached. Figure 5-7 As shown: Appendix Figure 5 SiO x The initial charge-discharge curves of the SiO2 composite material were obtained. The results indicate that SiO2... x The initial reversible capacity of the @C composite material is 924 mAh g. -1 The initial Coulomb efficiency was 64.4%.
[0043] Appendix Figure 6 SiO x The rate performance curves of the @C composite material were obtained at 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 Ag. -1 At current density, SiO xThe discharge specific capacities of @C were 985.6, 826.3, 685.2, 592.4, 501.3, and 386.5 mAh g, respectively. -1 When the current density recovers to 0.1 A g -1 At that time, SiO x @C's capacity can be restored to 962.4 mAh g -1 This demonstrates its excellent structural stability and reversibility, as well as its superior capacity reversibility.
[0044] Appendix Figure 7 and Figure 8 SiO x @C composite material at 1 A g -1 and 0.2 Ag -1 The cycling performance curves at current density show that the capacity retention rates after 200 cycles are 97.9% and 89.6% compared to the capacity after 20 cycles, respectively, indicating that the material has good cycling stability. Example
[0045] This embodiment describes a non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂. x The preparation method of the @C negative electrode, and the specific preparation steps are as follows: (1) Disperse 150 mg of siloxane nanosheets in 100 mL of deionized water and stir under ice bath conditions to form a uniform suspension.
[0046] (2) 100 μL of pyrrole monomer was slowly added under vigorous stirring. Then, after sonication at 300 W for 20 min, (NH4)2S2O8 solution was added dropwise as an oxidant, controlling the molar ratio of pyrrole to (NH4)2S2O8 to be 1:2 to initiate polymerization. The polymerization reaction was carried out continuously with stirring at 0 °C for 12 h.
[0047] (3) After completion, the product was thoroughly washed with deionized water until neutral and then vacuum dried at 80 °C for 12 h to obtain the Siloxene@PPy composite material.
[0048] (4) The prepared Siloxene@PPy precursor was placed in a Joule heating device and subjected to flash Joule heating (FJH) treatment by applying a large instantaneous current. The process achieved a heating temperature of about 700 °C and the heat treatment was completed after about 120 s.
[0049] (5) A non-equilibrium reaction environment was established by ultrafast heating and rapid quenching, and the target product SiO was finally obtained. x @C.
[0050] The material obtained in Example 3 was subjected to scanning electron microscopy (SEM) testing, and the results are as follows: Figure 9 The SiO shown x @C not only has a layered structure but also has a carbon layer coating. An electrode was fabricated using a paste made from active material, conductive agent, and binder in a ratio of 8:1:1. Constant current charge-discharge tests were then performed on it, with a yield of 1 A g. -1 SiO at current density x The charge-discharge curves of the first two charge-discharge cycles of the @C composite material are as follows: Figure 10 As shown, the results indicate that SiO x The reversible capacities of the @C composite material during the first two charge-discharge cycles were 563.7 mAh g. -1 537.7 mAh g -1 .
[0051] The SiO of the present invention x The @C composite material has a layered structure, with a continuous and uniform nitrogen-doped carbon coating layer constructed on the surface of the siloxane matrix. This nitrogen-doped carbon layer, on the one hand, constructs a long-range conductive network, significantly improving the intrinsic conductivity of the material; on the other hand, it effectively buffers the volume expansion of the siloxane matrix during charge and discharge, helping to maintain the integrity of the particle structure and the stability of the electrode interface. Therefore, the composite material prepared in this invention exhibits excellent cycle stability, high capacity retention, and low capacity decay during charge and discharge cycles.
[0052] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0053] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A non-equilibrium Joule heating method for preparing two-dimensional nitrogen-doped carbon-coated SiO₂ x The method and application of the @C negative electrode are characterized by... The SiO x The siloxane matrix of the @C composite material has a stacked layered structure in the vertical direction, with a continuously connected conductive carbon network and a uniform mesoporous structure distributed between the layers and on the planar surfaces of the lamellae. x The two-dimensional sheet planar dimensions of the @C composite material are 1 to 12 μm, and there are nanoscale gaps between any adjacent siloxene sheets that can buffer volume deformation. The width of the gaps is 10 to 120 nm.
2. A two-dimensional nitrogen-doped carbon-coated SiO2 as described in claim 1 x The preparation method of @C composite material is characterized by The product, prepared using the confined space of two-dimensional layered siloxanes and a non-equilibrium flash Joule heating process, includes the following steps: (1) Preparation of siloxane material: Prepare a hydrochloric acid solution with a concentration of 0.5-12 M. Under ice bath stirring, slowly add CaSi2 to the prepared hydrochloric acid solution. After the reaction is complete, wash the product with water until neutral, then perform ultrasonic exfoliation treatment, filter and freeze dry under vacuum to obtain siloxane material. (2) Preparation of composite precursor by in-situ polymerization: The siloxane material is dispersed in 50-100 mL of carbon source aqueous solution, and ultrasonically dispersed for 10-60 min under ice bath conditions. Then, an oxidant is added to initiate in-situ polymerization. After the reaction is carried out for 8-12 h, the product is washed with water until neutral, filtered and vacuum dried to obtain the composite precursor of the polymer of siloxane and the carbon source. (3) Carbonization treatment to obtain the target material: The above composite precursor is placed in a flash Joule heating device and subjected to instantaneous high-temperature carbonization treatment under an inert atmosphere. After the treatment is completed, two-dimensional nitrogen-doped carbon-coated SiO2 can be obtained. x @C composite material.
3. A two-dimensional nitrogen-doped carbon-coated SiO2 according to claim 2 x The preparation method of @C composite material is characterized by, In step (1), the ratio of CaSi2 to hydrochloric acid solution is 1 g: (20-300) mL, the ice bath reaction temperature is 0-10 ℃, and the reaction time is 20-30 h.
4. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... In step (2), the concentration of the siloxane material is 0.5–2 mg / mL. -1 .
5. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The carbon source mentioned in step (2) is a solution of 2-aminothiophene, aniline, pyrrole, o-aminophenol, and p-phenylenediamine. The mass ratio of the siloxane material to the carbon source is 1:(0.4-2), and the ultrasonic power of the dispersion process is 200-500 W.
6. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The oxidant mentioned in step (2) is a solution of FeCl3, (NH4)2S2O8, K2S2O8, Fe2(SO4)3, or Fe(NO3)3, and the molar ratio of carbon source to oxidant is 1:(1.5~2.5).
7. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The inert atmosphere mentioned in step (3) is a mixture of N2, Ar, or H2 / Ar.
8. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The specific operating parameters for the flash Joule heating described in step (3) are as follows: the heating rate is 10 3 ~10 4 Ks -1 The processing temperature is 500–900 ℃, and the processing time is 60–180 s.
9. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The stirring speed for water washing in step (1) is 200–600 r / min. -1 Wash until the pH of the filtrate is 6-7; the stirring speed for water washing in step (2) is 300-800 r / min. -1 The washing time is 2 to 6 hours.
10. The method for preparing two-dimensional nitrogen-doped carbon-coated SiO2 using non-equilibrium Joule heating according to claim 2. x The method for the @C negative electrode is characterized by... The drying method described in step (1) is freeze drying, the freeze drying time is 12 to 24 h, and the freeze drying temperature is -40 to -50 ℃; the drying method described in step (2) is vacuum drying, the vacuum drying temperature is 60 to 80 ℃, and the drying time is 8 to 12 h.
11. A two-dimensional nitrogen-doped carbon-coated SiO2 prepared by the method according to any one of claims 2-10 x The application of the C-type negative electrode in lithium-ion batteries is characterized by, The SiO x @C composite material is directly used as the negative electrode material for lithium-ion batteries; or the SiO2 composite material is used directly as the negative electrode material for lithium-ion batteries; x @C composite material is used as a negative electrode active material. After being mixed with conductive agents and binders, it is used as a negative electrode in high-energy-density lithium-ion batteries.